The Effect of Yoga Intervention on Psychological Symptoms, Health-Related Quality of Life, and Cardiovascular Risk Factors in People with Coronary Artery Disease: A Systematic Review and Meta-Analysis - Mansueto Gomes Neto; Michelli Bernardone Saquetto; Leonardo Roever; Vitor Oliveira Carvalho (Heart and Mind)
Background: Whether yoga is effective in the cardiac rehabilitation of people with coronary artery disease (CAD) remains controversial. Objective: The aim of this study was to investigate the effects of yoga intervention on psychological symptoms, health-related quality of life (HRQoL), and major cardiovascular risk factors in people with CAD. Methods: We searched MEDLINE/PubMed, Cochrane, EMBASE, and Physiotherapy Evidence Database (from the earliest date available to July 2023). Mean difference (MD), standardized MD (SMD), and 95% confidence interval (CI) were calculated. Results: Seventeen studies, with 5,698 patients, met the study criteria. Compared to control (no exercise), yoga resulted in improved depression MD −0.83 (95% CI: −1.35 to −0.31), stress MD −3.83 (95% CI: −4.8 to 2.86), HRQoL SMD 1.48 (95% CI: 0.55 to 2.4), major cardiovascular risk factors (peak VO2 MD 1.7 mL/kg/min [95% CI: 0.2 to 3.3], systolic blood pressure MD −3.2 mmHg [95% CI: −5.9 to −0.5], and diastolic blood pressure MD −2.42 mmHg [95% CI: −4.08 to −0.76]). Conclusions: Yoga was effective in the improvement of psychological symptoms, HRQoL, and cardiovascular risk factors.